Nail Isthmus: A Distinct Region of the Nail Apparatus - Naoki Oiso; Ichiro Kurokawa; Akira Kawada (Hindawi Limited, 2012)
The nail unit is constructed by distinctly regulated components. The nail isthmus is a lately proposed region as a transitional zone between the most distal part of the nail bed and the hyponychium. It is difficult to recognize the nail isthmus in the normal nail, but it is easy to identify the region in nail disorders such as pterygium inversum unguis and ectopic nail. We describe structure and putative function of the nail isthmus via histopathologic features of pterygium inversum unguis and ectopic nail.